The Relationship Between Spousal Support and Choice of Delivery Location Among Pregnant Women in Their Third Trimester at the Benao Community Health Center - Recka Ariyani Fitria Noor; Anik Purwati (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
The birth facilities and birth attendants are directly linked to maternal mortality. It has been demonstrated that births attended by healthcare professionals help lower the risk of maternal mortality. Traditional birth attendants and non-health personnel have a very restricted understanding of physiology and pathology, which leads to issues with delivery help, which are the primary reasons for high rates of maternal and perinatal mortality and morbidity. The significance of family support for selecting a birth attendant. At the Benao Community Health Center, this research sought to determine the link between husband support and the choice of birthplace among pregnant women in their third trimester. This study employed a descriptive analytical design with a cross-sectional methodology, which is a study to establish the existence of two relationships or a number of variables. In the meantime, the sampling method employed complete sampling, which resulted in a sample size of 30 individuals. In this study, a questionnaire was employed as the instrument. The data was then analyzed with SPSS using Chi Square analysis. After using the chi-square statistical test, a P-value (asymp. Sig 2-tailed) of 0.000 < 0.05 was found, indicating a correlation between the location of delivery chosen by pregnant women in their third trimester and the support of their spouses. As a result, since H0 was disproved and H1 was proven, it may be inferred that there is a link between a pregnant woman's choice of delivery location in her third trimester and the support she receives from her spouse.